A Catholic Inclusive Approach to Homosexuality in Nigeria - Asue, Daniel Ude (Theology today, 2018)
This essay discusses Same-Sex Marriage Prohibition Bill in Nigeria, with a focus on the contribution of the Nigerian Catholic Church to the law. Though the Catholic Church in Nigeria did not actively contribute towards the public debates about homosexuality that resulted into the Same-Sex Marriage Prohibition Bill it nevertheless welcomed the bill. However, the official teachings of the Catholic Church and elucidations from the Catholic Bishops Conference of Nigeria could potentially contribute to creating an inclusive society. In what way can we potentially utilize the principles of Catholic Social Teaching to make room for an inclusion of homosexual persons in the life of the church and in society?